The Preceptions of students and Teachers about The Level of The Sanctions for academic Integrity Violans: An Explanatory Sequential Design Study in a Nursing Education Program - Yogik Setia Anggreini; Yayi Suryo Prabandari; Titi Savitri Prihatiningsih (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2017)
Background: Professional Behavior is a reflection of the professionalism, which includes academic integrity. Some of student’s behavioral violations related to academic integrity are influenced by perception. However, students and lecturers tend to interpret these violations differently associated with severity of academic integrity, for example, the sanction against violations of academic integrity. Thus, these differences may contribute to the number of occurrences of academic integrity violations. This study aims to identify the perception of nursing students and lecturers about the level of sanctions for violations of academic integrity.Method: This study used a mixed method using a sequential explanatory design. This was also a quantitative research survey using a questioner to 101 nursing students, followed by focus group discussion done by the students and in-depth interviews to four lecturers.Results: The behavior deemed not to be in violation was 1% -5.9%. Most students chose sanction level 2 (21.8% - 66.35%), sanction level 3 (23.8% - 28.7%) and the highest sanction level or level 10 (19.8%)Conclusion: The perception of students to the sanction level out of 22 items, 15 items nursing students chose sanction level 2 “verbal warning” (21.8% - 66.35%), 2 items students chose sanction level 3 “written warning” (23.8% -28.7%). The highest sanction level chosen was level 10 “reported to the professional regulatory body” (19.8%). The lecturers assumed that mild sanction first given was in the form of verbal warning and the toughest was being suspended.